2017
DOI: 10.21010/ajtcam.v14i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Downregulates Cell Proliferation Markers During Dmba Induced Oral Carcinogenesis in Golden Syrian Hamsters

Abstract: Background: Cell-cycle disruption is the major characteristic features of neoplastic transformation and the status of cell-cycle regulators can thus be utilized to assess the prognostic significance in patients with cancer. The PCNA, cyclin D1, CDK4, CDK6 and survivin expression in the buccal mucosa was utilized to evaluate the Emodin efficacy on abnormal cell proliferation during 7,12-dimethylbenz(a)anthracene (DMBA) induced oral carcinogenesis in golden Syrian hamsters. Materials and methods: Topical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It exhibits remarkable biological effects such as anti-inflammation, anti-oxidant, prevention of intrahepatic fat accumulation and DNA damage [360][361][362][363][364][365][366]. Many studies have shown that emodin can attenuate numerous cancers including nasopharyngeal, gall bladder, lung, liver, colorectal, oral, ovarian, bladder, prostate, breast, stomach and pancreatic cancers, through the inhibition of cell proliferation and growth, metastasis, angiogenesis, and induction of apoptosis [367][368][369][370][371][372][373][374][375][376][377][378][379].…”
Section: Emodinmentioning
confidence: 99%
“…It exhibits remarkable biological effects such as anti-inflammation, anti-oxidant, prevention of intrahepatic fat accumulation and DNA damage [360][361][362][363][364][365][366]. Many studies have shown that emodin can attenuate numerous cancers including nasopharyngeal, gall bladder, lung, liver, colorectal, oral, ovarian, bladder, prostate, breast, stomach and pancreatic cancers, through the inhibition of cell proliferation and growth, metastasis, angiogenesis, and induction of apoptosis [367][368][369][370][371][372][373][374][375][376][377][378][379].…”
Section: Emodinmentioning
confidence: 99%
“…Ginsenosides extracted from Fax Chen, Panax ginseng, and cinnamon (Cinnamomum cassia Presl) can inhibit cell proliferation, migration, angiogenesis, and anti-drug resistance (49-57) Plays anti-cancer effects in colorectal cancer, breast cancer, liver cancer and lung cancer (32)(33)(34)(35). Emodin can be isolated from rhubarb palm, Polygonum cuspidatum, Polygonum multi orum and Cassia seed, which has anti-in ammatory, anti-oxidant, prevent hepatic fat accumulation and DNA damage (58)(59)(60)(61)(62)(63)(64) has been shown to slow nasopharyngeal cancer, gallbladder cancer, lung cancer, liver cancer, colorectal cancer, oral cancer, ovarian cancer, bladder cancer, prostate cancer, breast cancer, gastric and pancreatic cancer (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular ATP leads to increase of intracellular ATP concentration, thus promotes cell growth and survival of A549 cells [29]. Recent study shows that emodin inhibits cell proliferation by modulating cell cycle markers expression during oral carcinogenesis [38]. Subsequently, we investigated the effect of emodin on ATP-induced proliferation in A549 cells.…”
Section: Discussionmentioning
confidence: 99%